Embedding Synthetic Microvascular Networks in Poly(Lactic Acid) Substrates with Rounded Cross-Sections for Cell Culture Applications - Huang, Jen-Huang; Kim, Jeongyun; Ding, Yufang; Jayaraman, Arul; Ugaz, Victor M. (PloS one, 2013)
Synthetic microvascular networks are essential to enable in vitro studies of cell biology, biophysics, hemodynamics, and drug discovery, as well as in applications involving tissue engineering and artificial vasculature. But current limitations make it challenging to construct networks incorporating a hierarchy of microchannel diameters that possess cell-favored circular cross-sectional topographies. We report a new approach that overcomes these limitations by employing pressure-assisted expansion of biocompatible degradable poly(lactic acid) (PLA) substrates. This single-step process is straightforward and highly controllable, making it possible to simultaneously shape the interior topology of branched 3D and pseudo-3D microchannel networks across wide range of diameters. We further demonstrate in vitro culture of confluent endothelial cell monolayers in microchannel networks treated by this process, suggesting potential as a tool to help generate bio-mimicking vascular-like environments.